Analysis of the history of ball sports - Abdulsalam, Zahiah Sabah; Abdulameer, Wafaa Hussein; Hamza, Jamal Sakran (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Sports are one of the important topics that are still included a sub-topic in the school curricula. Ball sports are considered one of the most important sports in our societies today because of their wide and enthusiastic audience. The aim of the study was to analyze the history of ball games, namely football, handball, basketball and volleyball, and to study them as a general historical follow-up study with a simple initial formula. It was also aimed to study the importance of sports to humans. There is a close relationship between ball games and environmental conditions. The place and the climate had an impact on the discovery of some of these games. Some of them have a wide and likable audience, and some were practiced by a certain aristocracy, and had an ethnic influence on their practice because of their popularity. Others derived from a second game played with new atmospheres and new laws. As long as there is a development in human life in general and in the sports fields in particular, we will find that sports are required and renewed, and this development must result in the discovery of new games, which in turn will enter the competitive fields.